Automatic quadrilateral and hexahedral finite element mesh generation : review of existing methods - Mounoury, Valerie; Stab, Olivier (European Journal of Computational Mechanics, 2012)
In this paper, automatic quadrilateral and hexahedral mesh generation methods are reviewed. A classification is proposed and each method is explained. The first class deals with conversion techniques. In the second one, generation methods are studied. Decompositions into topologically simple subdomains are often used. Most of the methods deal with two dimensional mesh generation techniques and with their possible extension to three dimensional domains. A few recent techniques which produce hexahedral elements are presented. The industrial use of certain methods is mentioned.